Pengembangan Modul Berbantuan Augmented Reality Pada Mata Pelajaran Informatika - Dagu Nurhaliza Fitri Indra; Yogi Irdes Putra; Fitri Yanti (CV. DIGITIAL EDUKASI NUSANTARA, 2025)
This study aims to develop an Augmented Reality (AR)-assisted learning module as an innovative medium to enhance the effectiveness of Informatics learning, particularly hardware concepts, for seventh-grade students at SMP Negeri 1 Muara Bungo. The Research and Development (R&D) method with the 4D model (Define, Design, Development, Disseminate) was employed. Instruments include validation sheets for content and design experts, practicality questionnaires for teachers and students, and pretest–posttest learning assessments. Findings indicate that the module is highly valid (92.55% content experts, 86.85% design experts), highly practical (89% teachers, 85.6% students), and effective (87% classical completeness, paired t‑test = 7.024, indicating significant improvement between pretest and posttest). The study is limited to hardware material and seventh-grade level, limiting broader generalization. Practically, the module offers an interactive learning medium that boosts motivation and comprehension. Socially, it contributes to integrating educational technology in schools. Its originality lies in integrating a printed module with AR technology tailored to local needs, offering contextual and relevant learning experiences.